ANALISIS CURRENT RATIO, DEBT TO TOTAL ASSET RATIO,DEBT TO EQUITY RATIO, DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Suvianto Wangdra (JURNAL AKUNTANSI BARELANG, 2019)
The aim of this research is to determine the effect of the variables Current Ratio, Debt to Total Asset Ratio, Debt to Equity Ratio, and Net Profit Margin to the stock prices of food and beverage companies listed on the Indonesia Stock Echange for the period 2013-2017. The population in this research included food and beverage companies listed on the Indonesia Stock Exchange. The sampling technique on this research used was Purposive Sampling based on the following criteria: (1) Food and beverage companies listed on the Indonesia Stock Exchange, (2) Food and beverage companies listed on the Indonesia Stock Exchange which provide complete annual financial reports from 2013-2017, (3) Food and beverage companies that provide financial statements in Rupiah. By using purposive sampling, a total sample of 12 companies were acquired with a total of 60 observations. The data analysis technique used in this research is multiple linear regression analysis. Result show that Current Ratio, Debt to Total Asset Ratio,and Debt to Equity Ratio don’t have significant effect in stock prices of companies. Meanwhile, Net Profit Margin has a significant effect in stock prices of companies.